Initiation of business clinics and financial records assistance for SMEs/SMIs in Kucur Village, Malang Regency - Rino Tam Cahyadi; Yohanna Nirmalasari; Novenda Kartika Putrianto (University of Merdeka Malang, 2022)
The SMEs/SMIs sector is an important economic sector to develop. The development of this business sector can be done through community service activities for entrepreneurs. This activity was carried out in Kucur Village, Malang Regency, where many of the people are SMEs/SMIs entrepreneurs to earn additional income. However, many entrepreneurs do not understand bookkeeping or financial records. This community service activity is aimed at initiating the establishment of a business clinic and assisting in the preparation of financial records. The method of implementation includes forum group discussion, participant data collection, training, and mentoring. The findings show that there is no business clinic as a forum for entrepreneurs' aspirations, participants are dominated by housewives who own a business and do not have an understanding of financial records. The financial problems faced include there is no classification between business capital and own capital, business expenses that are not calculated into operational costs, as well as marketing problems. The results of the activity show that business clinics support the business development of entrepreneurs.